An Overview of Dry Eye Disease for Eye Care Professionals in Canada - Chan, Clara C. (Canadian Journal of Optometry, 2021)
Dry eye disease (DED) is a multifactorial ocular surface condition that is highly prevalent and often chronic, with significant associated burden. The 2017 report from the Tear Film & Ocular Surface Society Dry Eye Workshop II (TFOS DEWS II) is an in-depth look at all aspects of DED. Although TFOS DEWS II has comprehensively defined and classified the disease and summarized the current DED literature on a global scale, it does not highlight country-specific aspects of DED diagnosis and treatment options. In this review, we provide an overview of DED in the Canadian context, with an emphasis on DED identification, diagnosis, and treatment options available in Canada. In addition, we discuss needs and opportunities within the Canadian ophthalmic community regarding DED.